PENGARUH MOTIVASI TERHADAP KEPUASAN KERJA PEGAWAI - Yanti Yanti; Amirul Mukminin (Sekolah Tinggi Ilmu Ekonomi Semarang, 2021)
Abstract Work motivation is an encouragement of internal needs and encouragement by superiors in order to achieve optimal agency goals. The purpose of this study was to determine the effect of motivation on job satisfaction. The research method used is associative research with a quantitative approach, where variables are measured by a Likert scale. The data collection method was done by using a questionnaire. The population in this study were 42 employees of the Personnel and Human Resources Development Agency of Bima City, and the sample used was 35 respondents. Samples were taken using the SLOVIN formula. The sample technique used was purposive sampling, the data analysis techniques used were validity and reliability tests, simple linear regression and t-test. The results of this study indicate that motivation has a positive and insignificant effect on job satisfaction, with a significance value of 0.237 which is greater than the significance level α = 0.05. The insignificant influence in this study is due to the fact that the burden of work given to employees is already structured so that employees will automatically complete their tasks in accordance with their duties and responsibilities.